PeerWise: Evaluating the Effectiveness of a Web-Based Learning Aid in a Second-Year Psychology Subject. (July 2018) - Howe, Piers D. L.; McKague, Meredith; Lodge, Jason M.; Blunden, Anthea G.; Saw, Geoffrey
Testing can do more than just determine what a student knows; it can aid the learning process, a phenomenon known as the testing effect. There is a growing trend for students to create and share self-assessment questions in their subject, as advocated by the contributing-student pedagogy (CSP). For subjects with large enrolments, this process can be facilitated by educational technology. PeerWise is an example of such technology. It is free, web-based software that allows students to author, share, answer, and provide feedback on multiple-choice quizzes in a collaborative and constructivist fashion. While it is popular, it is unclear to what degree it facilitates student learning. To evaluate its effectiveness, we introduced PeerWise into a second-year psychology subject. We measured the extent to which it increased scores in the final exam. We found that PeerWise did significantly increase exam scores, so was a useful learning aid.